Cooling, exhumation, and kinematics of the Kanchenjunga Himal, far east Nepal. Issue 6 (5th June 2017) - Larson, Kyle P.; Camacho, Alfredo; Cottle, John M.; Coutand, Isabelle; Buckingham, Heather M.; Ambrose, Tyler K.; Rai, Santa Man
Abstract: New single crystal 40 Ar/ 39 Ar and apatite fission track ages from the Kanchenjunga region of far east Nepal yield insight into the timing of assembly of the Himalayan midcrust and the mechanisms that controlled its exhumation. The 40 Ar/ 39 Ar data are compared with new U(Th)/Pb zircon and monazite intrusive crystallization ages and existing metamorphic monazite ages from across the study area to test for internal consistency and potential excess Ar contributions. This new data set, which significantly enhances the density and spatial coverage available from the region, shows that inferred thrust‐sense discontinuities within the now‐exhumed former midcrustal rocks exposed therein must have ceased motion by ~12 Ma. Furthermore, the spatial distribution of ages across the Kanchenjunga region, older ages (~12–16 Ma) to the south and north and younger ages (~8 Ma) in the middle portion of the transect, is compatible with simulations of tectonic‐enhanced exhumation above a developing duplex system in nearby Bhutan. Key Points: New single crystal 40 Ar/ 39 Ar and apatite fission track ages significantly enhance the available data in the study region 40 Ar/ 39 Ar ages from across the Kanchenjunga region do not show an association with inferred thrust‐sense discontinuities Thermochronologic data are compatible with tectonic‐enhanced exhumation above a developing duplex system